Analysis of Drug Utilization and Drug - drug Interactions in Outpatients with Dyslipidemia at Buon Ma Thuot Medical University Hospital, November 2024 - January 2025 - Khoang, Le Trung; Huyen, Hoang Thi Thu; Vinh, Ha Hoang Anh; Quynh, Huynh Thi Nhu; Linh, Doan Phuong; Thu, Nguyen Hoan (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
This study aimed to analyze the patterns of drug utilization and drug-drug interactions among outpatients treated for dyslipidemia. A cross-sectional descriptive study was conducted on 498 prescriptions. Descriptive statistics were used for demographic and drug utilization characteristics. drug-drug interactions were evaluated using three databases: Micromedex, Drugs.com, and Medscape. The Chi-square test or Spearman's correlation was employed to investigate factors influencing drug-drug interactions. The results showed that the mean age of patients was 55.79 ± 11.58 years, with a female majority (54.02%). The most common comorbidities were gastrointestinal diseases (42.57%). The median number of active ingredients per prescription was 3 (Interquartile Range: 2-5). Non-pharmacological lipid-lowering therapy was utilized by 9.23% of patients. Statins were the most prescribed drug class (83.93%), with long half-life statins like rosuvastatin and atorvastatin being the most frequent choices (76.90%), the prevalence of potential drug-drug interactions was 12.65%. Factors significantly associated with drug-drug interactions included the number of active ingredients per prescription, the presence of comorbidities, and the use of niacin (p < 0.05). These findings suggest that close monitoring for drug-drug interactions is warranted for patients on polypharmacy and with comorbidities, particularly the elderly, to ensure treatment efficacy and safety. Keywords: Prescription, outpatient, dyslipidemia, drug utilization, drug interactions.